2015
DOI: 10.5430/crcp.v2n4p36
|View full text |Cite
|
Sign up to set email alerts
|

Acute cocaine-induced hepatotoxicity with features of shock liver

Abstract: Background: Cocaine-induced toxicity has been described to be associated with severe adverse clinical health outcomes, affecting multiple organs systems with very limited clinical recommendations or guidelines for management of some of its associated complications. Case report:We present a case of middle-aged female with acute severe hepatotoxicity after ingestion of alcohol and non-intravenous cocaine. She had markedly elevated liver enzymes and lactate dehydrogenase suggestive of shock liver but with minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Similarly, cocaine may cause hepatocyte damage through two mechanisms: hypoperfusion and oxidative stress. It has been suggested that cocaine reduces hepatic blood flow, causing shock liver, or ischemic hepatitis [10,11]. The findings of shock liver have been associated with cocaine-induced hepatitis in several case reports [9,[11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cocaine may cause hepatocyte damage through two mechanisms: hypoperfusion and oxidative stress. It has been suggested that cocaine reduces hepatic blood flow, causing shock liver, or ischemic hepatitis [10,11]. The findings of shock liver have been associated with cocaine-induced hepatitis in several case reports [9,[11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient presented with fulminant hepatitis that manifested with all of the above-mentioned symptoms secondary to acute cocaine toxicity in the setting of β-blocker use. Cocaine has been reported to cause hepatotoxicity in humans [1][2][3][4][5][6] as well as several animal models. [7][8][9][10][11] Two previous studies found cocaine use to be associated with hepatic dysfunction manifested by elevation in liver enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these findings give pertinence to further research relating to the long‐term damage that cocaine induces in organ systems involved in detoxification. Though there have been clinical reports relating to cocaine‐induced hepatoxicity such as Adedinsewo, Ajao, Okpobrisi, Fotzeu, and Crawford (), a limitation exists in research relating to the molecular mechanisms driving its pathological significance that concentrate on the cell cytoskeleton in the hepatic microenvironment. Research suggests that cocaine may be able to mediate HSC activation through several well‐known pro‐fibrotic mediators such as PDGF and TGF‐β.…”
Section: Future Perspectivementioning
confidence: 99%